1997
DOI: 10.1093/ije/26.4.739
|View full text |Cite
|
Sign up to set email alerts
|

Association of leisure time physical activity with the risk of coronary heart disease, hypertension and diabetes in middle-aged men and women

Abstract: The results suggest a preventive effect of leisure time physical activity on CHD, hypertension and diabetes. This effect may differ among middle-aged men and women and the relative importance of the total amount and the intensity may vary depending on the outcome measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
147
4
17

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(185 citation statements)
references
References 0 publications
17
147
4
17
Order By: Relevance
“…Further results from the Nurses Health Study suggested that, independently of exercise levels, sedentary behaviours, especially TV watching, were associated with significantly elevated risk of type 2 diabetes and obesity, whereas even light to moderate activities were associated with a substantially lower risk [24]. Also, an inverse association between exercise and incidence of type 2 diabetes was observed among residents of the UK [21,25] and Finland [13,26]. The findings in the present study extend the literature showing that leisure time physical activity is associated with a reduction in risk of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Further results from the Nurses Health Study suggested that, independently of exercise levels, sedentary behaviours, especially TV watching, were associated with significantly elevated risk of type 2 diabetes and obesity, whereas even light to moderate activities were associated with a substantially lower risk [24]. Also, an inverse association between exercise and incidence of type 2 diabetes was observed among residents of the UK [21,25] and Finland [13,26]. The findings in the present study extend the literature showing that leisure time physical activity is associated with a reduction in risk of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…AT Adipose tissue; CRF Cardiorespiratory fitness; LT Lean tissue; WC Waist circumference; WL Weight loss decreased by 6% (61). Results of other prospective studies in men and women further suggest that high levels of physical activity protect against the incidence of coronary artery disease, independent of BMI, as well as other factors such as age, smoking, diabetes and hypertension (62). Furthermore, prospective analyses from the Aerobics Center Longitudinal Study have consistently reported that CRF is a significant predictor of mortality from all causes (9,10,63,64), CVD (9,10) and type 2 diabetes (65) in men and women, independent of BMI or WC.…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 91%
“…For the women both a higher total amount of activity and weekly vigorous activity had an inverse association with the risk of diabetes (Haapanen, Miilunpalo, Vuori, Oja, & Pasanen, 1997).…”
Section: Phq-9 Score ≤4 (No Depression)mentioning
confidence: 90%